Peningkatan Hasil Belajar PPKN dan Keaktifan Siswa Melalui Model Pembelajaran Pamer Pada Siswa Kelas V SDN NO 145 INPRES BAYOWA Kabupaten Takalar - Nurlianna Nurlianna; Abdul Azis; Syamsuriyanti Syamsuriyanti (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The purpose of this study was to improve civics learning outcomes and student activity through the PAMER learning model for fifth grade students at SDN No. 145 Bayowa Presidential Instruction, Takalar Regency. The research conducted was classroom action research (PTK). This research was conducted in two cycles which included four meetings. The subjects of this study were 21 students of class V SDN No 145 Bayowa Presidential Instruction, Takalar Regency, consisting of 11 boys and 10 girls. Data collection techniques are observation, test (evaluation), and documentation. The data obtained were then analyzed using quantitative and qualitative descriptive analysis.The results achieved quantitatively are (1) The application of the PAMER learning model in student activity, response and learning outcomes of class V SDN No 145 Inpres Bayowa Takalar Regency, namely an increase in student activity and courage in each cycle, where student activity in cycle I with an average score - average 49.3 in the less active category increased in cycle II to 88.1 in the very active category. Student responses in cycle I with an average of 66.1 categories responded to an increase in cycle II with an average of 80.9 categories of very responsive. (2) Improving PPKn learning outcomes and student learning activities in accordance with the results of observations during the class action process. The average score obtained by students after taking the final test from cycle I to cycle II after the learning model was applied increased from 59.3 in cycle I to 87.9 in cycle II. The completeness of learning PPKn for fifth grade students at SDN No. 145 Bayowa Presidential Instruction, Takalar Regency, has also increased. In cycle I, from 9 (42.8%) students to cycle II as many as 18 (85.7%) students achieved mastery learning and classical learning mastery reached 80%.